Covert bacteriuria in schoolgirls in Newcastle upon Tyne: A 5-year follow-up†. Issue 8 (August 1981) - ,
Abstract : Two hundred and fifty-two schoolgirls with covert bacteriuria were followed up for 5 years. Forty-one girls were prescribed obligatory chemotherapy because of renal involvement, mainly scarring. Of the remaining 211 girls, 106 were randomly allocated to a no chemotherapy group and 105 to a chemotherapy group to receive a 2-year course of chemotherapy. Treatment was highly effective with 98% showing some response bacteriologically and 90% being culture-negative at 2 years. However, at 5 years—that is 3 years after stopping treatment—this had fallen to 64%. In the no chemotherapy group 40% had spontaneously become culture-negative at 2 years and this had increased to 49% at 5 years. The difference at 5 years between the two groups attains statistical significance. During follow-up, 11% of the no chemotherapy group and 9·5% of the chemotherapy group developed symptomatic disease of the urinary tract. Renal growth was measured by calculating regression lines for the relationship between kidney length and the distance between the 1st and 3rd lumbar vertebrae. The rate of growth of the kidneys over 5 years in the two randomised groups was similar. Only one girl (no chemotherapy group) developed a new renal scar during the study. Measurement of the growth rate of individual kidneys in the obligatory chemotherapy group showed that, despite chemotherapy, there was below average growth in 21 out of 33 scarred kidneys and in 8 patients the degree of renal scarring had increased. It was concluded that, when kidneys were radiologically normal, covert bacteriuria did not lead to renal damage or impaired renal growth in the subsequent 5 years, even if it remained untreated. Consequently, it is recommended that schoolchildren should not be screened for covert bacteriuria until a non-radiological method can be devised to detect those with renal scarring.